(untitled) (Journal of the Management Sciences, 2025)
Leveraging technological devices to enhance contents for public communication such as speeches, remarks, addresses and public lectures can improve the relationship between organisations and their publics. However, despite the growing rate of misinformation and hate speech in the information ecosystem, dearth of empirical data on knowledge and usage of AI has been particularly acute in Africa including Nigeria. Hence, this study aims to assess Imo public relations professionals’ Knowledge and usage of AI for public communication. The study was guided by specific objectives including to: determine level of knowledge on AI potentials, extent of usage of AI for public communications and factors that can facilitate adaptation among the PR professionals in Imo state. Technological determinism underpins the study. An estimated population of 99 registered public relations professionals were examined using the survey research method. The census principle was adopted based on the manageability of the population size. Questionnaire was the instrument for data collection designed in a modified 5-point Likert scale. Analysis of data involved frequency counts and percentage. Whereas the mean served as the statistical tool. Results indicated a high level of knowledge of AI potential for public communications at a mean of 3.7, while level of usage was found to be moderate at a mean of 2.7. Training and retraining PR officers to keep them abreast of AI technology and provision of support devices and tools to facilitate adaptation were recommended.